Community Service Strengthening Goat Livestock Group in Catur Village, Kintamani-Bangli District - Sudita, I Dewa Nyoman; Situmeang, Yohanes Parlindungan; Swedi, I Komang; Nahak, Stefanus; Damayanti, Ni Luh Putu Sulis Dewi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
The province administration of Bali consistently promotes the formation of livestock farming communities, namely in goat farming, using housing and livestock aid initiatives. The "Subak Abian Pebunut" goat farming group in Catur Village, Kintamani District, Bangli, is among the recipients of government aid in goat farming. Despite its relatively short duration of operation, the group above needs support and instruction, particularly in maintenance management and feeding techniques. This is particularly relevant in effectively utilizing a substantial quantity of coffee waste via fermentation. The primary objective of this community service initiative is to modify the behavior of individuals within the group. Specifically, the focus is on enhancing their knowledge, abilities, and attitudes. It is important to note that the delivered content is derived from prior research studies. The approach employed in this community service initiative involves disseminating educational resources, followed by practical instruction on the fermentation of coffee skins. Additionally, trials and evaluations are conducted on goats to assess their growth and gauge their response to the practices above. The implementation of community service has yielded notable outcomes in knowledge acquisition, specifically in the discovery of the potential for fermenting coffee skins to produce animal feed of superior quality. In terms of actual implementation, the active involvement of all group members is ensured to facilitate the subsequent execution of the probiotic component blending and coffee skin fermentation procedures. In the context of trials and assessments, it was seen that the administration of fermented coffee skins to goats yielded notable outcomes in terms of their growth, as opposed to a control group of goats that did not get coffee skins. Based on the findings of this community service initiative, it can be inferred that the participants expressed satisfaction in acquiring knowledge and hands-on experience in producing fermented feed using coffee skins. Additionally, they observed the direct impact of feeding fermented coffee skins to livestock over one month, specifically examining the animals' response to consumption and its influence on the growth of goats.